The Effect of Round Robin Technique Toward Students’ Speaking Performance at MTS. Muhammadiyah Pulau Punjung - Desnita, Mona; Irwandi, Irwandi; Eliza, Eliza; Safitri, Loli (Journal of Educational Management and Strategy, 2022)
This research is triggered by students' speaking performance problems. The first problem is related to the fact the srudents still cannot  speak fluently and accurately. Secondly, students still have low confidence in practicing speaking skills. Thirdly, students did not have an English mastery strategy. This study aimes as finding do not significant effect of the round robin technique to improve students' speaking performance in terms of their fluency and accuracy in practicing interpersonal dialogue. This research was an experimental research. In collecting data researcher used pretest-posttest control control  design. The  experimental group was VIII.A (23 students ) and control group that was VIII.B (23 Students). The sample was selected by using total sampling technique. The data was got through pre-test and post-test to experimental and control groups. The research findings indicates that,the result of post-test in experimental class has t-obtained (59.25) was higher than t-table (1.6802) with degree of freedom (df) = 0.05. Thus, the alternative hypothesis (ha) was accepted which means that there was significant effect of using Round Robin Technique toward students speaking performance. Thus, it can be concluded that the intire hypothesis was accepted. It was proved that Round Robin Technique could help students in improving and enggaging their speaking and Round Robin Technique is recomended to be lesed by english lesson in teaching speaking. Abstrak Latar belakang penelitian ini dipicu oleh masalah kinerja berbicara siswa. Masalah pertama adalah siswa tidak dapat berbicara  dengan lancar  , kedua  siswa masih memiliki kepercayaan yang  rendah dalam melatih kemampuan berbicara, yang ketiga siswa tidak memiliki strategi penguasaan bahasa inggris. Penelitian ini bertujuan untuk menemukan pengaruh yang signifikan dari teknik Round Robin untuk meningkatkan kinerja berbicara siswa dalam kefasihan dan ketepatan mereka dalam mempraktikan dialog interpersonal. Penelitian ini menggunakan penelitian eksperimen. Dalam pengumpulan data peneliti menggunakan pretest-posttest control design. Terdapat kelompok eksperimen VIII.A (23 siswa) dan kelompok kontrol yaitu VIII.B (23 siswa). Sampel dipilih dengan menggunakan teknik total sampling. Data diperoleh melalui pre-test dan post-test pada kelompok eksperimen dan control. Hasil penelitian menunjukkan bahwa dari nilai pre-test dan post-test kelas eksperimen, t-hitung (59,25) lebih besar dari t-tabel (1,6802) dengan derajat kebebasan (df) = 0,05. Oleh karena itu, hipotesis alternatif (ha) diterima yang berarti bahwa ada pengaruh yang signifikan dari Teknik Round Robin terhadap kinerja berbicara siswa. Dengan demikian dapat disimpulkan bahwa hipotesis inti diterima. Terbukti bahwa Teknik Round Robin dapat membantu siswa meningkatkan dan melibatkan berbicara mereka dan Teknik Round Robin lebih baik daripada Teknik konvensional.